Mencari Format Ideal Keadilan Putusan dalam Peradilan - Bambang Sutiyoso (Jurnal Hukum IUS QUIA IUSTUM, 2010)
The law enforcement procedures that has been running these days are still strongly hold on the form of procedural justice that urges the regulation aspect and the application of law in formal way only. As the impact, the trial to commit a fair law become less qualified or in the other word, it cannot solve the core of the problem. This research talks about a problem relating with the question about how to find an ideal format of justice on giving judgment in a court. This study uses normative juridical approach. Meanwhile, the data for this research are taken from the secondary data by using the analysis method of qualitativedescriptive. The result of the research shows that on handling a law’s case, a judge should not only see from law’s perspective only that is related with the procedural justice, but also he should see the substantive justice. As the consequence, it would be very advantageous if the procedural and the substantive justice can be combined and accommodated in the right proportion. But in a case where those two forms of justice cannot be compromised, then it is suggested to make the substantive justice as the first priority.Key words : Decision, substantial justice, procedural justice